Calculation of Water Supply to Hydraulic Jet Devices - M. V. Krautsou; A. M. Krautsou (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Dependence for calculation of working fluid supply to water-air ejector is proposed. The dependence has been derived via analysis and processing of data being obtained by experimental research of water-jet devices.